2018
DOI: 10.1136/annrheumdis-2017-212617
|View full text |Cite
|
Sign up to set email alerts
|

Differential ubiquitination in NETs regulates macrophage responses in systemic lupus erythematosus

Abstract: This is the first study to find ubiquitinated proteins in NETs, and evidence for adaptive immune responses directed towards ubiquitinated NET proteins in SLE. The distinct differences in ubiquitin species profile in NETs compared with healthy controls may contribute to dampened anti-inflammatory responses observed in SLE. These results also support a role for extracellular ubiquitin in inflammation in SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 53 publications
2
58
1
2
Order By: Relevance
“…Barrera-Vargas et al (60) reported, as the current study was underway, that stimulation with LPS-induced NETs led to an enhanced production of TNF-a and IL-10 in macrophages from patients with SLE when compared with controls, and this was dampened when macrophages were treated with chloroquine, an inhibitor of endosomal acidification and lysosomal enzyme activity. Because acidic pH of endosomes is a prerequisite of endosomal TLR activation, chloroquine is frequently used as an antagonist for endosomal TLRs, and the results thus suggest that TLR signaling is partly implicated (60). Moreover, these findings underscore that responses to NETs in healthy individuals and in patients with autoimmune diseases may differ.…”
Section: Discussionmentioning
confidence: 48%
“…Barrera-Vargas et al (60) reported, as the current study was underway, that stimulation with LPS-induced NETs led to an enhanced production of TNF-a and IL-10 in macrophages from patients with SLE when compared with controls, and this was dampened when macrophages were treated with chloroquine, an inhibitor of endosomal acidification and lysosomal enzyme activity. Because acidic pH of endosomes is a prerequisite of endosomal TLR activation, chloroquine is frequently used as an antagonist for endosomal TLRs, and the results thus suggest that TLR signaling is partly implicated (60). Moreover, these findings underscore that responses to NETs in healthy individuals and in patients with autoimmune diseases may differ.…”
Section: Discussionmentioning
confidence: 48%
“…Less clear, and worth of further investigation, is the contribution of cit-LL37 to the immunogenicity of LL37 in psoriasis, a disease characterized by decreased citrullinated proteins in hyperproliferative epidermis, but also by neutrophil infiltrate 61 . Also, we are aware that the role of citrullination in autoreactivity in SLE could be restricted to the LL37-directed response, as additional post-translational modifications are reasonably considered dominant in SLE 62 . Of interest for the rheumatology field, the correlation between T-cell responses and antibody levels, and of both responses with disease activity (SLEDAI), renders LL37-directed responses interesting biomarkers, at least in patients that respond to LL37.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the main pathogenic role of LDNs/LDGs in autoimmunity appears to be largely related to their enhanced ability, relative to autologous NDNs, to expose autoantigens through the release of NETs [96]. In this context, NETs released by LDNs/LDGs obtained from the peripheral blood of SLE patients contain, compared with NETs from autologous or healthy control circulating NDNs, elevated amounts of immunogenic antigens such as oxidized mitochondrial DNA [103] and citrullinated or ubiquitinated antigens that can activate plasmacytoid dendritic cells or macrophages [96,104]. Moreover, in RA patients, NET-derived citrullinated antigens from circulating neutrophils have been recently found to be phagocytosed and presented to in vitro generated antigen-specific CD4 + T cell clones by synovial fibroblasts, which in turn can trigger the generation of autoantibodies that contribute to inflammation [105].…”
Section: Neutrophil Diversity and Heterogeneity In Chronic Inflammationmentioning
confidence: 99%